The Significance Of Preserving The Historical Architectural Legacy Of Uzbekistan (Journal of Architectural Design, 2024)
The preservation of Uzbekistan's architectural heritage, particularly the unique style of Uzbek eclecticism, can be achieved through the use of 3D printing technology as an effective restoration tool. 3D printing allows for the restoration of lost decorative elements and complex architectural features with high precision, resulting in cost savings. Recent developments in 3D technology and materials offer new opportunities for developing environmentally friendly solutions that are adapted to the climate of Central Asia. The scientific value of this research lies in evaluating the potential and challenges of innovative techniques, contributing to the development of methods for preserving cultural heritage and applying them in architectural restoration projects.